2011
DOI: 10.1098/rstb.2010.0343
|View full text |Cite
|
Sign up to set email alerts
|

Social learning in birds and its role in shaping a foraging niche

Abstract: We briefly review the literature on social learning in birds, concluding that strong evidence exists mainly for predator recognition, song, mate choice and foraging. The mechanism of local enhancement may be more important than imitation for birds learning to forage, but the former mechanism may be sufficient for faithful transmission depending on the ecological circumstances. To date, most insights have been gained from birds in captivity. We present a study of social learning of foraging in two passerine bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 96 publications
4
100
0
Order By: Relevance
“…preference for the personal-poor feeder (time spent near the personal-poor feeder minus time spent near the personal-rich feeder from instantaneous sampling every 6 s for 90 s) in the personal-information only condition ('control', white bar), the social-information only conditions (black bars, where 3-3 denotes three fish shoaling at one feeder and three fish at the other feeder) and the public-information conditions (hashed bars, where 3P-3R denotes three fish feeding at the public-poor feeder and three fish at the public-rich feeder, respectively While many animals, notably chimpanzees [13], orangutans [14] and capuchin monkeys [15], exhibit behavioural traditions in nature (see [16][17][18]), the evidence that these are underpinned by social learning is, at best, circumstantial, leading to considerable controversy over the legitimacy of claims of animal culture [8,19]. In contrast, for fish there exists highly compelling experimental evidence that natural traditions are maintained through social learning, stemming from transplant experiments (see also [20]). Helfman & Schultz [21] transplanted French grunts, Haemulon flavolineatum, between populations and found that the moved individuals subsequently learn the daily migration routes between the foraging and resting sites used by resident conspecifics.…”
Section: Social Learning In Fishesmentioning
confidence: 99%
“…preference for the personal-poor feeder (time spent near the personal-poor feeder minus time spent near the personal-rich feeder from instantaneous sampling every 6 s for 90 s) in the personal-information only condition ('control', white bar), the social-information only conditions (black bars, where 3-3 denotes three fish shoaling at one feeder and three fish at the other feeder) and the public-information conditions (hashed bars, where 3P-3R denotes three fish feeding at the public-poor feeder and three fish at the public-rich feeder, respectively While many animals, notably chimpanzees [13], orangutans [14] and capuchin monkeys [15], exhibit behavioural traditions in nature (see [16][17][18]), the evidence that these are underpinned by social learning is, at best, circumstantial, leading to considerable controversy over the legitimacy of claims of animal culture [8,19]. In contrast, for fish there exists highly compelling experimental evidence that natural traditions are maintained through social learning, stemming from transplant experiments (see also [20]). Helfman & Schultz [21] transplanted French grunts, Haemulon flavolineatum, between populations and found that the moved individuals subsequently learn the daily migration routes between the foraging and resting sites used by resident conspecifics.…”
Section: Social Learning In Fishesmentioning
confidence: 99%
“…In this review, we synthesize existing knowledge of the importance of social learning in wild animal societies, with a focus on non-primate mammals (primates [10,11], birds [12] and fish [13] are topics of other contributions in this issue, and we discuss research on these and other taxa where relevant). We concentrate particularly on research at our long-term field site of cooperatively breeding meerkats (Suricata suricatta), where access to multiple groups of individually recognizable, habituated animals has allowed us to obtain detailed records of individual development and enabled experimental tests of social learning.…”
Section: Introductionmentioning
confidence: 99%
“…A final (6th) exposure session before testing lasted 1 hr, to ensure that chicks were completely avoiding the aposematic feeders. Notably, our group exposure training procedure allows for social learning (Slagsvold & Wiebe, 2011) as the chicks in the same cage may learn from each other's negative reaction to the feed in aposematic feeders. The learned aversion from conspecifics is still a theme that deserves investigation as contrasting results have been reported (Sherwin, Heyes, & Nicol, 2002; Thorogood et al., 2017).…”
Section: Methodsmentioning
confidence: 99%